Pengaruh Artificial Intelligence, Big Data Dan Otomatisasi Terhadap Kinerja SDM Di Era Digital - Arya Satya Pratama; Suci Maela Sari; Maila Faiza Hj; Moh Badwi; Mochammad Isa Anshori (Jurnal Publikasi Ilmu Manajemen, 2023)
Purpose - The digital era has fundamentally transformed the business landscape, presenting new challenges and opportunities for Human Resources (HR) management. This article investigates the effects of the utilization of Artificial Intelligence (AI), Big Data, and Automation on HR performance in an increasingly digital business environment. Findings - This research aims to identify how these technologies influence HR, both positively and negatively. Design/methodology/approach - Research methods include surveys, data analysis, and case studies across various industries. The results indicate that the presence of AI has altered how HR handles routine tasks. AI enables HR to optimize recruitment processes, deliver tailored training, and forecast future workforce needs. Big Data has become a valuable resource in HR decision-making. Data collected from various sources allows for in-depth analysis of employee performance, workplace happiness, and productivity trends. Automation has also reshaped the job landscape by taking over repetitive tasks, freeing up HR to focus on more strategic work. Practical implications - However, this research also underscores several challenges. Organizational culture changes are required to effectively integrate these technologies, and concerns about data privacy need to be addressed with stringent policies. Originality/value - In conclusion, the use of Artificial Intelligence, Big Data, and Automation has a significant impact on HR performance in the digital era. Organizations capable of integrating these technologies with an innovative work culture will emerge as leaders in optimizing their human resources and gaining a competitive edge in the ever-evolving digital age.